Negotiating Normative Expectations, Problematic Sustainability and Disempowerment: The Conflicting Realities of Participation Practices in the Estonian Civil Society - Kitsnik, Joanna (Studies of Transition States and Societies, 2020)
Participation is a right held by all community members to engage in decision-making processes. The negotiation power of individuals and interest groups expressed through participatory practices is especially valuable in a young democracy with a short history of civil society and community initiative. Researching participation opens new perspectives into local agency and helps to identify various powers and ideologies in action. Estonian civil society has made notable progress since the country regained its independence, but participatory practices have neither improved in quality nor increased in volume. Furthermore, previous research indicates a discrepancy between normative expectations and empirical reality. This paper draws on a comparative study from 2016 and examines the differences between the Estonian non-profit and the public sectors’ experiences and expectations regarding participation practices. The qualitative content analysis method was employed on the interviews conducted with a total 65 public and third sector representatives. The results are contextualised through critical theories of participation which regard participation as a complex, multidimensional and strongly ideologised solution. The study concludes that the promises of empowerment typical to the mainstream participation rhetoric are yet to be rooted in the practices of participation in Estonian civil society, where instead the repeating motif in the participatory experience is disempowerment.